Endorsement of alternative medicine and vaccine hesitancy among physicians: A cross-sectional study in four European countries - Angelo Fasce; Linda Karlsson; Pierre Verger; Otto Mäki; Frederike Taubert; Amanda Garrison; Philipp Schmid; Dawn Liu Holford; Stephan Lewandowsky; Fernanda Rodrigues; Cornelia Betsch; Anna Soveri (Taylor & Francis Group, 2023)
Vaccine hesitancy has become a threat to public health, especially as it is a phenomenon that has also been observed among healthcare professionals. In this study, we analyzed the relationship between endorsement of complementary and alternative medicine (CAM) and vaccination attitudes and behaviors among healthcare professionals, using a cross-sectional sample of physicians with vaccination responsibilities from four European countries: Germany, Finland, Portugal, and France (total N = 2,787). Our results suggest that, in all the participating countries, CAM endorsement is associated with lower frequency of vaccine recommendation, lower self-vaccination rates, and being more open to patients delaying vaccination, with these relationships being mediated by distrust in vaccines. A latent profile analysis revealed that a profile characterized by higher-than-average CAM endorsement and lower-than-average confidence and recommendation of vaccines occurs, to some degree, among 19% of the total sample, although these percentages varied from one country to another: 23.72% in Germany, 17.83% in France, 9.77% in Finland, and 5.86% in Portugal. These results constitute a call to consider health care professionals' attitudes toward CAM as a factor that could hinder the implementation of immunization campaigns.